2021
DOI: 10.1128/aem.00122-21
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Inulin Increases Lactiplantibacillus plantarum Strain Lp900 Persistence in Rats Depending on the Dietary-Calcium Level

Abstract: Synbiotics are food supplements that combine probiotics and prebiotics to synergistically elicit health benefits in the consumer. Lactiplantibacillus plantarum strains display high survival during transit through the mammalian gastrointestinal tract and were shown to have health-promoting properties. Growth on the fructose polysaccharide inulin is relatively uncommon in L. plantarum, and in this study we describe the plasmid-encoded β-fructosidase (FosE) with inulin hydrolyzing properties of L. plantarum strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…In a mouse colitis model, Son et al (2019) showed that a synbiotic composed of Lactobaccillus GG and tagatose was superior to Lactobaccillus GG and tagatose alone in inhibiting inflammatory responses [62]. Fuhren et al (2021) showed that inulin increased the intestinal persistence of inulin consuming bacterium L. plantarum Lp900 contained in the synbiotic [63]. Studies also showed that the synbiotic Bacillus coagulans MTCC5856 and sugarcane fiber produced more profound effects than B. coagulans and sugarcane fiber alone in inhibiting inflammation and producing SCFAs in a colitis model [64,65].…”
Section: Synbioticsmentioning
confidence: 99%
“…In a mouse colitis model, Son et al (2019) showed that a synbiotic composed of Lactobaccillus GG and tagatose was superior to Lactobaccillus GG and tagatose alone in inhibiting inflammatory responses [62]. Fuhren et al (2021) showed that inulin increased the intestinal persistence of inulin consuming bacterium L. plantarum Lp900 contained in the synbiotic [63]. Studies also showed that the synbiotic Bacillus coagulans MTCC5856 and sugarcane fiber produced more profound effects than B. coagulans and sugarcane fiber alone in inhibiting inflammation and producing SCFAs in a colitis model [64,65].…”
Section: Synbioticsmentioning
confidence: 99%
“…Previously, we have shown that dietary inulin significantly increases intestinal persistence of inulin-utilizing Lactiplantibacillus plantarum Lp900 when administered in a high calcium diet context. 12 Inulin utilization by L. plantarum Lp900 is driven by extracellular degradation of this substrate, which may compromise the competitive advantage of this capacity by “hitchhiking” of other species or strains that are equally efficient in utilizing the released breakdown products (i.e., predominantly fructose monosaccharides; Supplemental Figure SF1). 13 In contrast, we have previously shown that the variable utilization of GOS (i.e., DP2 versus DP3–4 (HDP) GOS) by L. plantarum strains depends on the strain-specific HDP-GOS-import capacity followed by intracellular metabolization of these substrates, 14 which eliminates the “hitchhiking” possibility for competing strains (Supplemental Figure SF2).…”
Section: Introductionmentioning
confidence: 99%
“…18 When probiotics and prebiotics are combined together into synbiotics, they work together in synergy to provide a better effect compared to that achieved when probiotics or prebiotics are administered alone. 19,20 Studies have found that synbiotics can regulate the gut microbiota, which contributes to a healthy intestine environment and enhances nutrient absorption in the body. [21][22][23] Rodrigues showed that synbiotics help increase bone mineral concentrations, thereby preventing osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Prebiotics have been shown to increase the abundance of Lactobacillus plantarum and improve the intestinal calcium absorption under the conditions of a low-calcium diet. 19 Prebiotics are used in high-calcium foods to improve the performance of probiotics and reduce the risk of osteoporosis in the elderly. 27,28 With the aim of developing a dietary calcium product that can supplement calcium in an efficient manner, this study combined prebiotics with probiotics and added them to normal milk powder to prepare a new type of milk powder product with additional benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation